Permanent photodoping of plasmonic gallium-ZnO nanocrystals. Issue 12 (12th March 2020) - Zukuls, Anzelms; Eglītis, Raivis; Käämbre, Tanel; Ignatans, Reinis; Šmits, Krišjānis; Rubenis, Kristaps; Začs, Dzintars; Šutka, Andris
Abstract : The concentration of delocalized electrons in plasmonic metal oxide nanocrystals can be increased permanently by photodoping because the electron compensation becoming the dominant compensation mechanism for the aliovalent donor dopant. Abstract : Donor dopants in oxide semiconductors are compensated not only by valuable electrons but also by other point defects, leading to a decrease in electric conductivity and infrared absorption. We demonstrate that the electron compensation mechanism in Ga doped ZnO nanocrystals can be promoted by photodoping. Unexpectedly, the electrons from photodoping are stable in the open air for months.